Holistic Monitoring Model Based on Islamic Theology in the Education Management Control System - Samsuri Samsuri; Akhmad Sukardi; Hasan Basri (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
This article examines the limitations of conventional management control mechanisms, which tend to focus on structural and procedural controls. It proposes a holistic supervision model based on Islamic theology to align personnel work behavior with organizational goals in a more sustainable manner. This study aims to develop a comprehensive conceptual framework of supervision that integrates organizational supervision, transcendental supervision, and self-supervision as a unified control system. The research employs a qualitative approach through a systematic literature review, examining management books, national and international journal articles, as well as classical and contemporary Islamic theology literature obtained from Google Scholar, Dimensions, DOAJ, and the SINTA portal. The data were analyzed using content analysis techniques in a critical paradigm to identify patterns of relationships between formal control mechanisms and individual spiritual awareness. The results of the study show that supervision based solely on organizational structure tends to produce formalistic and situational compliance. Conversely, the integration of transcendental supervision, based on the belief in Allah SWT's supervision and eschatological accountability, with faith-based self-supervision has proven to be the most effective foundation for shaping integrity, honesty, and consistency in work behavior. Organizational supervision functions optimally when positioned as a complement that supports individual internal control. This study recommends a paradigm shift in leadership from coercive supervision to the cultivation and internalization of spiritual awareness, thereby building an effective, ethical, and sustainable management control system, particularly in the context of Islamic education management.